Exercise intensity and oxygen uptake kinetics in African-American and Caucasian women - Lai, Nicola (2011)
The effect of exercise intensity on the on- and off-transient kinetics of oxygen uptake (VO(2)) was investigated in African American (AA) and Caucasian (C) women. African American (n=7) and Caucasian (n=6) women of similar age, body mass index and weight, performed an incremental test and bouts of square-wave exercise at moderate, heavy and very heavy intensities on a cycle ergometer. Gas exchange threshold (LT(GE)) was lower in AA (13.6±2.3mL·kg(−1)min(−1)) than C (18.6±5.6mL·kg(−1)min(−1)). The dynamic exercise and recovery VO(2) responses were characterized by mathematical models. There were no significant differences in 1) peak oxygen uptake (VO(2peak)) between AA (28.5±5mL kg(−1)min(−1)) and C (31.1±6.6mL kg(−1)min(−1)) and 2) VO(2) kinetics at any exercise intensity. At moderate exercise, the on- and off- VO(2) kinetics was described by a mono-exponential function with similar time constants τ(1,on) (39.4±12.5s;38.8±15s) and τ(1,off) (52.7±10.1s;40.7±4.4s) for AA and C, respectively. At heavy and very heavy exercise, the VO(2) kinetics was described by a double-exponential function. The parameter values for heavy and very heavy exercise in the AA group were respectively: τ(1,on) (47.0±10.8;44.3±10s), τ(2,on) (289±63;219±90s), τ(1,off) (45.9±6.2;50.7±10s), τ(2,off) (259±120;243±93s) while in the C group were respectively: τ(1,on) (41±12;43.2±15s); τ(2,on)(277±81;215±36s), τ(1,off) (40.2±3.4;42.3±7.2s), τ(2,off) (215±133;228±64s). The on- and off-transients were symmetrical with respect to model order and dependent on exercise intensity regardless of race. Despite similar VO(2) kinetics, LT(GE) and gain of the VO(2) on-kinetics at moderate intensity were lower in AA than C. However, generalization to the African American and Caucasian populations is constrained by the small subject numbers.